“I wanted to learn something. I just couldn't”—Autistic students‘ perspectives on emotions as drivers of absenteeism and attendance - Sasso, Isabella (Frontiers in Education, 2025)
IntroductionThe right to education is recognized as a fundamental human right in international law. Despite these legislative foundations, education systems still often fail to recognize and provide the necessary accommodations and support needed by many autistic students. Studies on mainstream schooling of autistic students predominantly report negative experiences, as their needs are not adequately addressed, leading to stress and anxiety. Attendance at mainstream schools has also been identified as a potential risk factor for school attendance problems. In Germany, research on the school experiences and absences of autistic students remains scarce. The present study therefore aims to investigate the role of emotions in the development of school attendance problems among autistic students in mainstream school settings in Germany.MethodsThe study employed a constructivist grounded theory design. Semi-structured interviews were conducted with 20 autistic students between 7 and 20 years, who experienced school attendance problems within the German mainstream school system. Interviews were transcribed with high level of accuracy to capture how emotions were expressed. The interviews analyzed through iterative coding, including initial, focused, and theoretical coding. In-vivo codes were applied to preserve participants' perspectives and generate a theory grounded in the data.ResultsFindings show that autistic students experience school attendance as stressful and exhausting due to sensory overload and barriers in reciprocal interaction with peers and teachers. Stress accumulated over time, resulting in anxiety, panic, anger, and exhaustion, which directly contributed to school absenteeism. Students used strategies to adapt and endure the environmental factors, which did not regulate but rather intensified their stress. At the same time, positive emotions such as the desire to learn, willingness to attend or return to school, and hope to re-engage occured as central motivational drivers for attendance. Results highlight the importance of environmental factors in shaping students' ability to fulfill their desire to learn and attend school.DiscussionThe study adds to existing literature by centering autistic students' perspectives and demonstrating how emotional experiences contribute to school attendance and absenteeism. The findings underscore the need for strength-based, flexible, and context-sensitive approaches. Future research is required to examine educational outcomes and wellbeing of students in mainstream schools.